"Do the Best You Can with Resources You Have to Offer": Community stakeholder views on supporting immigrant families. Issue 3 (22nd November 2022) - Edwards, Nicole Megan; Isik‐Ercan, Zeynep; Lu, Huan‐Tang; Fall, Madjiguene; Sebti, Latifa
Abstract: First and second‐generation immigrant families of young children in the United States face potential challenges that may be mitigated with stakeholder support in their communities. We examined self‐reported views and behaviors among professionals ( n  = 76) working with families in a mid‐Atlantic urban community, and whether these views correlated with demographic factors. Over half of respondents were not able/willing to report the number of immigrant families served and over half believed immigrant parents are less likely to advocate for themselves or their child. Participants were fairly split in seeking advice from others and comfort in talking with immigrant families about their culture/needs. It is essential to assess stakeholders' views on perceived roles, roadblocks, and desired supports. This analysis informs efforts to work more collaboratively with community partners to improve outreach to immigrant families during those formative years in a child's development. Implications for research, practice, and policy are discussed.